A busca pelo parto natural e motivações para o preparo do assoalho pélvico com o epi-no - Santos, Silvana dos (Universidade Federal de São Carlos, 2015)
This work entitled "The search for natural childbirth and motivations to prepare the pelvic diaphragm with the epi-no" has as main objectives: to understand the elements involved in the choice of women for natural childbirth, identify motivations for the preparation of the pelvic diaphragm with the epi-no, seeking natural childbirth and identify the components that facilitate and those that hinder this choice. Was carried out with women who were part of the Epi-no Program, Health Laboratory initiative of Women of University of São Paulo, between 2013 and 2014. This is a qualitative research, for which we used as theoretical and methodological approach, Feminism Dialogic proposed by Lygia Puigvert (2001) and the Critical Communicative Methodology (MCC) proposed by Gomez et al (2006), both anchored in theoretical frameworks of Dialogic Learning, which in turn are based on concept of Communicative Action Habermas (1999) and dialogical of Paulo Freire (1994; 2005). The MCC seeks to identify the transformative dimensions, that is, those that promote or facilitate, in this case, a pleasurable experience of childbirth and cause difficulties dimensions, that is, those that represent a barrier to this experience, both relating to the categories of life and world system. Data collection began in November / 2013, and the analysis was organized as the basic level of analysis proposed by the MCC. Eight women were interviewed, seven of them completed the two phases of the communicative account, according to the methodology and there was canceling an interview, due to loss of material. The women were between 22 and 38 years with predominance of age above 30 years, all had a partner, five were primiparous (1st pregnancy) and two multiparous (2 or more pregnancies), with a history of cesarean section and abortion and all performed in childbirth hospital environment. The results showed that the discovery of pregnancy urged to talk with family, friends and health professionals about natural childbirth; aroused the personal search for information (books, magazines, internet, support groups natural childbirth); motivated to prepare the pelvic diaphragm with epi-no, among others. Childbirth, previously seen as traumatic and surrounded interventions (oxytocin, episiotomy, Kristeller) and suffering, in general gained a new meaning, exchanging a traumatic experience for a autonomous, self-control, fulfilling and unforgettable experience. The dimensions that transformed the labor context were linked to the experience of women and were related to world of life category. The analysis showed that they were more promising than category system, in other words , institutions, spaces, organization systems and guidelines governed by power or money. The processing dimensions were represented by groups who take the initiative to provide the dissemination of knowledge to women or who brought innovations (epi-no equipment, for example). In the case of cause difficulties dimensions, it was observed that the elements that related to the system and those related to the world of life is presented in similar numbers, showing that the woman is motivated to prepare the natural birth is difficult, both in his personal / family life, as in institutions. This work demonstrated that the changes initiated in the world of life category and that women rethought their way to see the birth, overcame their fears and naturelly tried to "convince" people around them. In the population studied was noted that the epi-no reduced lacerations, episiotomies warned, however in some cases did not prevent lacerations 1st degree. It is hoped that this work contribute to reflections on the delivery care model in order to rescue the female autonomy in childbirth and reduce myths and anxiety around the issue, reaffirming the importance, both from a personal point of view as a social and epidemiological , to follow the recommendations of the World Health Organization, as regards the issue of labor and birth.
Keywords: Enfermagem obstétrica; Parto normal; Humanização do parto; Nascimento; Humanized birth; Natural childbirth; Term birt; Epi-no; CIENCIAS DA SAUDE::ENFERMAGEM